Targeted O-glycoproteomics for the development of diagnostic markers for advanced colorectal cancer - Takakura, Daisuke; Ohashi, Shoko; Kobayashi, Noritoshi; Tokuhisa, Motohiko; Ichikawa, Yasushi; Kawasaki, Nana (Frontiers in Oncology, 2023)
Aberrant glycosylation is a prominent feature of cancer, that can be used as targets to improve the existing cancer biomarkers, and help to assess metastasis risks, and therapeutic effects. We developed a targeted O-glycoproteomics method using serum specimens, and evaluated its utility in identifying advanced colorectal cancer (CRC) markers. To this end, we combined consecutive lectin affinity purification using Maclura pomifera lectin (MPL), jacalin, and Sambucus nigra lectin, which have affinities for the following O-glycans, that have received attention as cancer-related antigens, Tn (GalNAc-Ser/Thr), Sialyl Tn (Siaα2-6GalNAc-Ser/Thr), T (Galβ1-3GalNAc-Ser/Thr), Sialyl T (Siaα2-3Galβ1-GalNAc-Ser/Thr), and di-Sialyl T (Siaα2-3Galβ1-3[Siaα2-6] GalNAc-Ser/Thr), with a unique O-glycoproteomics approach. A total of 2,068 O-glycoforms derived from 265 proteins were identified in healthy individuals and patients with advanced CRC, of which 44 CRC-specific O-glycoforms were extracted. Particularly, five glycoproteins with T, Sialyl T, and di-Sialyl T antigens in specific peptide regions were evaluated quantitatively and statistically. We found that fibulin-2 (FBLN2) (aa330-349 and aa365-378)/T antigen (area under the curve [AUC] = 0.93 and 0.92); macrophage colony-stimulating factor 1 (CSF1) (aa370-395)/ (T + di-Sialyl T) (AUC = 0.94); macrophage mannose receptor 1 (MRC1) (aa1083-1101 and aa1215-1229)/T (AUC = 0.95 and 1.00); fibrinogen alpha chain (FGA) (aa559-573)/Sialyl T (AUC = 0.91); and complement component C7 (C7) (aa692-701)/di-Sialyl T (AUC = 0.94), can have high diagnostic efficacy to strategically predict advanced CRC groups. Hence, they could be promising markers for detection of advanced CRC, and provide new clinical test indicators along with lectins, such as MPL and jacalin. Our O-glycoproteomics platform provides a novel tool and resource, for researchers and clinicians seeking to better understand and treat advanced CRC.